Correlated Cryo Super‐Resolution Light and Cryo‐Electron Microscopy on Mammalian Cells Expressing the Fluorescent Protein rsEGFP2. Issue 12 (13th August 2019) - Tuijtel, Maarten W.; Koster, Abraham J.; Faas, Frank G. A.; Sharp, Thomas H.
Abstract: Super‐resolution light microscopy (SRM) enables imaging of biomolecules within cells with nanometer precision. Cryo‐fixation by vitrification offers optimal structure preservation of biological specimens and permits sequential cryo electron microscopy (cryoEM) on the same sample, but is rarely used for SRM due to various technical challenges and the lack of fluorophores developed for vitrified conditions. Here, a protocol to perform correlated cryoSRM and cryoEM on intact mammalian cells using fluorescent proteins and commercially available equipment is described. After cell culture and sample preparation by plunge‐freezing, cryoSRM is performed using the reversibly photoswitchable fluorescent protein rsEGFP2. Next, a super‐resolved image is reconstructed to guide cryoEM imaging to the feature of interest. Finally, the cryoSRM and cryoEM images are correlated to combine information from both imaging modalities. Using this protocol, a localization precision of 30 nm for cryoSRM is routinely achieved. No impediments to successive cryoEM imaging are detected, and the protocol is compatible with a variety of cryoEM techniques. When the optical set‐up and analysis pipeline is established, the total duration of the protocol for experienced cryoEM users is 3 days, not including cell culture. Abstract : Cryo‐super resolution microscopy (cryoSRM), when correlated with cryo‐electron microscopy (cryoEM), permits the precise localisation of biomolecules within optimally‐preserved cellular ultrastructure. Here, a comprehensive protocol is presented to perform cryoSRM correlated with cryoEM on mammalian cells, including sample preparation, super‐resolution imaging and correlation. Data analysis and super‐resolution reconstruction protocols are described in detail, and computational scripts and a test‐dataset are provided.